Analysis of Revenue from Contracts with Customers for Motor Vehicle Financing in Accordance PSAK Number 72 at PT Hasjrat Multifinance Manado - Damar, Jeivi; Pangerapan, Sonny; Mawikere, Lidia M (PT FORMOSA CENDEKIA GLOBAL, 2024)
Revenue is very important for a company because it affects the expected profit level and determines the company's sustainability. Therefore, revenue must be recognized, measured, presented, and disclosed fairly in accordance with applicable standards, namely the Financial Accounting Standards (SAK), specifically PSAK No. 72 regarding Revenue from Contracts with Customers. This study aims to determine the revenue from contracts with customers for motor vehicle financing in accordance with PSAK No. 72 at PT Hasjrat Multifinance Manado. The analytical method used in this thesis research is descriptive qualitative. The results obtained from the study indicate that PT Hasjrat Multifinance Manado recognizes, measures, presents, and discloses its revenue in accordance with PSAK No. 72.